Pengaruh Nilai Tukar dan Suku Bunga terhadap Harga Saham Perbankan yang Terdaftar di Bursa Efek Indonesia - Yohanis Rohi Riwu; Ni Luh Ketut Ayu Sudha Sucandrawati; Made Winda (PT. PENERBIT TIGA MUTIARA, 2025)
This study aims to empirically analyze the effect of exchange rates and interest rates on the stock prices of banking companies listed on the Indonesia Stock Exchange during the 2020-2024 period. The research employs a quantitative approach with a causal-associative design and utilizes secondary data obtained from official publications of Bank Indonesia (BI) and the Indonesia Stock Exchange (IDX). The research population consists of 45 banking companies, from which 20 companies meeting the sampling criteria were selected using purposive sampling. Data analysis was conducted comprehensively through descriptive analysis, classical assumption tests, multiple linear regression, and hypothesis testing with the assistance of SPSS software. The findings reveal that, partially, exchange rates have a significant negative effect on stock prices, and interest rates also exert a significant negative effect. Furthermore, simultaneous testing confirms that both independent variables significantly and negatively influence banking stock prices. These results highlight that macroeconomic volatility, particularly exchange rate fluctuations and interest rate movements, are crucial determinants to be considered in capital market analysis. Academically, this study contributes to the literature on the relationship between macroeconomic indicators and stock price dynamics, while practically, the results may serve as a reference for investors in making investment decisions, for policymakers in formulating economic stabilization strategies, and for banking institutions in anticipating market risks arising from both global and domestic economic uncertainty.